Inhibiting tumor oxygen metabolism and simultaneously generating oxygen by intelligent upconversion nanotherapeutics for enhanced photodynamic therapy. (August 2020) - Wang, Dan; Xue, Bin; Ohulchanskyy, Tymish Y.; Liu, Yubin; Yakovliev, Artem; Ziniuk, Roman; Xu, Mengze; Song, Jun; Qu, Junle; Yuan, Zhen
Abstract: Hypoxia is one of the hallmarks of solid tumor, which heavily restricts the clinical cancer therapy treatments, especially for the oxygen (O2 ) -dependent photodynamic therapy (PDT). Herein, an intelligent multi-layer nanostructure was developed for decreasing the O2 -consumption and elevating the O2 -supply simultaneously. The cell respiration inhibitor –atovaquone (ATO) molecules were reserved in the middle mesoporous silicon layer, and thus were intelligently released at the tumor site after the degradation of gatekeeper of MnO2 layer, which effectively inhibit tumor respiration metabolism to elevate oxygen content. Meanwhile, the degradation of MnO2 layer can generate O2, further boosting oxygen content. Moreover, the inner upconversion nanostructures as the near infrared (NIR) light-transducers enable to activate photosensitizers for deep-tissue PDT. Systematic experiments demonstrate that this suppressing O2 -consumption and O2 -generation strategy improved oxygen supply to boost the singlet oxygen generation to eradicate cancer cells under NIR light excitation. Better still, superior trimodality imaging capabilities (computed tomography (CT), NIR-II window fluorescence, and tumor microenvironment-responsive T1-weighted magnetic resonance (MR) imaging) of the nanoplatform were evaluated. Our findings offer a promising aproach to conquer the serious hypoxia problem in cancer therapy by turning down the O2 metabolism aveneue and simultaneously generating O2 .